Diterpenes Isolated from Three Different Plectranthus Sensu Lato Species and Their Antiproliferative Activities against Gynecological and Glioblastoma Cancer Cells - Gáborová, Mária; Vágvölgyi, Máté; Tayeb, Bizhar Ahmed; Minorics, Renáta; Zupkó, István; Jurček, Ondřej; Béni, Szabolcs; Kubínová, Renata; Balogh, György Tibor; Hunyadi, Attila (ACS omega, 2024)
Fourteen diterpenes were isolated from methanol extracts of the aerial parts ofColeus comosus,Coleus forsteri "Marginatus", and Plectranthus ciliatus. The compounds belong to the abietane (1-4, 9-11, and 13), ent-clerodane (5-8), and ent-kaurane (14, 15) classes. Three new compounds were isolated from C. comosus, including 3-O-acetylornatin G (2), 3,12-di-O-acetylornatin G (3), ornatin B methyl ester (5), and ornatin F (4), for which we proposed a revised structure. The structures of the compounds were determined by comprehensive spectroscopic data analysis. The isolated diterpenes were examined in silico for their physicochemical and early ADME properties. Their antiproliferative effects were determined in vitro using human breast (MDA-MB-231 and MCF-7), cervical (HeLa), and glioblastoma (U-87 MG) cancer cell lines. The royleanone- and hydroquinone-type abietane diterpenes (9-13)exhibited the most potent antiproliferative activity against all cancer cell lines tested, particularly against glioblastoma cells, with IC50 values ranging from 1.1 to 15.6 μM.